Preoperative skeletal muscle index vs the controlling nutritional status score: Which is a better objective predictor of long‐term survival for gastric cancer patients after radical gastrectomy? - Zheng, Zhi‐Fang (Cancer Med, 2018)
Skeletal muscle index (SMI) and the controlling nutritional status (CONUT) score are useful for evaluating nutritional status, which is closely associated with cancer prognosis. This study compared the prognostic value of these indicators in patients with gastric cancer (GC) after radical gastrectomy (RG). We retrospectively enrolled 532 patients between 2010 and 2011. SMI was measured via CT images to determine low SMI. The CONUT score was calculated based on serum albumin, total lymphocyte count, and cholesterol. Patients were grouped according to SMI and the CONUT score based on previous research. Spearman's correlation coefficient, the Kaplan‐Meier method, and Cox regression were used. There was no significant correlation between SMI and the CONUT score. Five‐year overall survival (OS) and recurrence‐free survival (RFS) in patients with low SMI were significantly worse than those in patients with high SMI (P < .001). The normal nutrition group had better OS and RFS than did the light and moderate or severe malnutrition groups (P < .05), but the OS and RFS were not significantly different between the light and moderate or severe malnutrition groups (P = .726). Univariate analysis showed that SMI and the CONUT score were associated with OS and RFS, but only SMI remained prognostic in multivariate analysis. Preoperative SMI based on CT images is a more objective predictor than the CONUT score of long‐term survival in GC after RG, but this finding must be confirmed by prospective trials.